2018
DOI: 10.5194/acp-18-1977-2018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous acid formation in a snow-free wintertime polluted rural area

Abstract: Abstract. Nitrous acid (HONO) photolysis is an important source of hydroxyl radicals (OH) in the lower atmosphere, in particular in winter when other OH sources are less efficient. The nighttime formation of HONO and its photolysis in the early morning have long been recognized as an important contributor to the OH budget in polluted environments. Over the past few decades it has become clear that the formation of HONO during the day is an even larger contributor to the OH budget and additionally provides a pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 93 publications
3
30
1
Order By: Relevance
“…Another emerging question is the role of nitrifying microbes in the production of HONO, which is a major source of atmospheric OH and NO (28). Vertical gradients of HONO have been observed with the highest concentrations at ground level (29)(30)(31)(32), indicating that HONO production may be a function of biotic and/ or abiotic soil processes. Most studies have implicated abiotic mechanisms associated with NO x (NO and NO 2 ) chemistry as the primary driver of HONO production.…”
Section: Significancementioning
confidence: 99%
“…Another emerging question is the role of nitrifying microbes in the production of HONO, which is a major source of atmospheric OH and NO (28). Vertical gradients of HONO have been observed with the highest concentrations at ground level (29)(30)(31)(32), indicating that HONO production may be a function of biotic and/ or abiotic soil processes. Most studies have implicated abiotic mechanisms associated with NO x (NO and NO 2 ) chemistry as the primary driver of HONO production.…”
Section: Significancementioning
confidence: 99%
“…2. Given the focus of this work on the use of ANN to model nocturnal HONO chemistry, the Introduction and results should do a much better review and contrast to the existing capabilities of other models such as CMAQ (Czader et al, 2012;Diao et al, 2016;Gonçalves et al, 2012) or custom models Tsai et al, 2018;Vogel et al, 2003;Wong et al, 2012). The Authors should review this literature to aid in preparations for the re-running of their ANN.…”
Section: Interactive Commentmentioning
confidence: 99%
“…Line 304: The Authors conclude here that aerosol surfaces are important, but their lack of awareness of literature reports on the role of the ground surface relative to aerosol surfaces being far more important suggests that they need to reconsider their interpretation of the data after more thoroughly reviewing the literature (see references given in Major Comments above). All vertically-resolved HONO measurements have shown that the ground is a major sink for HONO, as well as dew and available surface water (He et al, 2006;Rubio et al, 2009;Stutz et al, 2004;Tsai et al, 2018;VandenBoer et al, 2015;Wojtal et al, 2011).…”
Section: C6mentioning
confidence: 99%
“…The Authors should revisit this. It would be better to show that typical aerosol uptake coefficients used by (Tsai et al, 2018;Wong et al, 2012) fail to produce the observed quantities of HONO and to quantify the fraction that aerosol conversion represents so it is clear that aerosol conversion is trivial.…”
Section: C6mentioning
confidence: 99%